Evaluating rice lipid content, yield, and quality in response to nitrogen application rate and planting density - Chen, Guangyi; Li, Congmei; Hu, Mingming; He, Xingmei; Yang, Hong; Zhang, Qiuqiu; Wu, Chaoyue; Duan, Qiang; Peng, Ligong; Zhang, Yao; Li, Ziyu; Ouyang, Yuyuan; et al. (Frontiers in Plant Science, 2024)
To investigate the effects of nitrogen (N) application rate and planting density (D) on the contents of lipid and free fatty acid, fatty acid composition, yield and quality of rice grain, a field experiment was conducted using Koshihikari (japonica) as experimental material from 2021 to 2022 with three N levels (90, 150 and 210 kg ha-1, denoted as N1, N2 and N3, respectively) and three transplanting densities (19.0 × 104, 26.7 × 104 and 40.0 × 104 plants ha-1, denoted as D1, D2 and D3, respectively). The results showed that N application rate and planting density had highly significant impacts only on the contents of free fatty acid and saturated fatty acid, respectively. Increased N and planting density enhanced the contents of lipid (29.41 mg g-1) and free fatty acid (21.47%). The highest values were obtained under N3D3 increasing by 7.02% and 3.23 percentage points, respectively, compared to other treatments. No significant differences in lipid content were found among treatments, whereas free fatty acid exhibited significant differences. The unsaturated fatty acid content increased with increasing N but first decreased and then increased with increasing planting density, while saturated fatty acid content showed the opposite trend. Appropriate N level and planting density improved the relative chlorophyll content and net photosynthetic rate of rice flag leaves, as well as increased grain yield, effective panicle number and spikelete number per panicle, but decreased the seed setting rate. Under N2D2, the relative chlorophyll content and net photosynthetic rate remained relatively high throughout the grain filling stage, resulting in the highest grain yield, with increases of 43.87-47.03% compared to other treatments. A moderate N level improved the milling quality of rice, while increased planting density reduced it. However, both increased N and planting density reduced the appearance quality and cooking and eating quality of rice. Overall, the effects of increasing N application rate and planting density on enhancing rice lipid and free fatty acid contents were limited. A combination of 150 kg ha-1 N application rate and 26.7 × 104 plants ha-1 was recommended for achieving relatively higher yield, lipid content and better grain quality.